The Impact of Corporate Social Responsibility on Economic Growth in the Region - N. S. Bezuglaya (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article studies problems of civilization development, which implies the conflict of interests of business proprietors, big multinational corporations and society urge towards sustainable development. The UN goals of sustainable development include environment protection, improving wellbeing of countries and overcoming poverty. Multinational corporations and regional enterprises stick to principles of corporate social responsibility, which partially comply with goals of sustainable development, but orient towards support of business proprietors’ wellbeing. Trends in global economy show that some multinationals by the level of their profits surpass the majority of countries. Thus, economic giants can render serious impact on state policy of the region, environmental situation and population prosperity. But companies and proprietors are interested only in allocating resources to developing countries, which prevents them from working for the goals of sustainable development. According to UN reports, confrontation and conflict between capital and society resulted in slow and complicated realization of goals of sustainable development. The author put forward a number of steps aimed at elimination of misbalance towards predominance of goals of sustainable development.